High-strength, high-hardness and high-entropy alloy with amplitude-modulated decomposition structure and preparation method thereof
High-strength, high-hard, high-entropy alloy prepared by vacuum arc smelting method uses optimized element ratio to form an amplitude-modulated decomposition structure of a single BCC phase, solving the problems of hard embrittlement and fatigue peeling of existing high-entropy alloys under cavitation load impacts. , achieving excellent cavitation resistance and cavitation-corrosion resistance.
Patent Information
- Application Number
- CN202411689070.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-18
AI Technical Summary
Existing high-entropy alloys are prone to hard brittlement and fatigue peeling under the impact of cavitation loads, resulting in poor cavitation resistance.
A high-strength, high-hard, high-entropy alloy with amplitude-modulated decomposition structure was prepared by vacuum arc smelting. The optimized element ratio was used to make the alloy components sit within the inflection point curve of the free energy-component curve, forming an amplitude-modulated decomposition structure of a single BCC phase.
This high entropy alloy exhibits excellent cavitation resistance and cavitation-corrosion resistance in deionized water and artificial seawater, has an ultimate compressive strength of 1.8~2.2 GPa and a nanohardness of 7.9~8.7 GPa, which is suitable for use in the following areas: Overflow components such as impellers, thrust bearings.
Smart Images

Figure CN119464887A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of advanced metal materials, and in particular relates to a high-strength, high-hardness, high-entropy alloy with a spinodal decomposition structure and a preparation method thereof. Background Art
[0002] Cavitation is a special form of erosion during wear, which is mainly caused by the high-frequency impact of high-pressure shock waves or high-speed microjets released by the collapse of cavitation liquid on the surface of nearby components. Cavitation is widely present on the surfaces of flow-through components in the fields of hydraulic machinery, ship engineering and fuel pumps, such as turbine blades, marine propellers, rudders, impellers and thrust bearings, causing huge economic losses and posing serious risks to the safe operation of equipment. The reason why the above-mentioned flow-through components are so severely damaged by cavitation is largely attributed to the fact that most of the metal materials used to make them are multi-phase structures, and the mechanical properties of different phases vary greatly. Under load impact, the degree of plastic deformation is different, and it is easy to form a "lip-shaped" convex structure, so it tends to break and peel quickly (Wear, 2015, 332-333, 1070-1079).
[0003] In order to better resist the high-frequency impact of cavitation loads, high-entropy alloys that tend to form simple solid solution structures have become the main front for people to develop new anti-cavitation materials. The invention patent with publication number CN115505811B, "An Al-Cr-Co-Ni series high-entropy alloy and its preparation method and application", discloses a dual-phase high-entropy alloy with a face-centered cubic structure (FCC phase) as the main phase and a body-centered cubic structure (BCC phase) evenly distributed. Its yield strength is 350~620 MPa, which is higher than the nickel-aluminum bronze (α+β+κ) with a more complex phase structure. Ⅰ +κ Ⅱ +κ Ⅲ +κ Ⅳ ) shows better cavitation-corrosion resistance. However, since this high-entropy alloy uses FCC as the main phase, its mechanical properties are relatively low. Under the repeated action of cavitation loads, the surface will become hard and brittle due to the accumulation of a large number of dislocations and other structural defects due to plastic deformation, followed by fatigue spalling (ACS Applied Materials&Interfaces, 2023,15 (2), 3651-3663). Therefore, how to improve the strength of high-entropy alloys and improve their ability to resist plastic deformation under load impact is an important exploration direction to further improve the material's cavitation resistance.
[0004] A major feature of high entropy alloys is that even if the alloying elements used are the same or similar, as long as the ratios are different, it is entirely possible to prepare new high entropy alloy materials with completely different structures (Nature, 2019, 574, 223-227), which provides a lot of room for people to design various types of cavitation-resistant materials. Yin Danqing et al. reported a high entropy alloy with BCC phase as the main phase and FCC phase evenly distributed. Although it has higher hardness, its cumulative mass loss after cavitation for 10 hours is as high as about 16 mg, and its cavitation resistance is worse (Materials, 2020,13, 4067). This is because although the BCC phase has fewer slip systems and is relatively more resistant to deformation, the mismatch in the deformation degree of the two phases cannot be avoided under the impact of strong cavitation loads, and the lack of toughness of the BCC phase promotes the formation and expansion of fatigue cracks. Therefore, the ability of this high entropy alloy to resist cavitation damage is lower.
[0005] That is to say, although high entropy alloys can easily form simple solid solution phases, there are still many difficulties in developing a long-lasting anti-cavitation material. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a high-strength and high-hardness high-entropy alloy with an amplitude modulated decomposition structure and a preparation method thereof, which can not only be obtained by simple smelting, but also does not require any subsequent heat treatment process and deformation strengthening process. The ingot can exhibit excellent comprehensive mechanical properties of high strength and high hardness, can effectively resist the deformation behavior caused by cavitation load impact, and exhibits excellent anti-cavitation and anti-cavitation-corrosion performance in both deionized water and artificial seawater, and is more suitable for use as a long-term protective material for many flow-through components such as impellers, thrust bearings, and rudders.
[0007] 1. Preparation of high entropy alloys A method for preparing a high-strength, high-hardness, high-entropy alloy with a spinodal decomposition structure is prepared by a casting method, including but not limited to a vacuum arc melting process. Taking the vacuum arc melting method as an example, the main preparation process is as follows: (1) Prepare pure metal raw materials containing Al, Cr, Co and Ni according to the mass percentage converted from the atomic percentage of the high entropy alloy, clean the crucible at the same time, then put the prepared raw materials into the crucible of a vacuum arc melting furnace, and place a titanium block in another crucible for absorbing oxygen; (2) Close the furnace door and evacuate the equipment to a vacuum degree of <1×10 -2 Pa, then fill with argon to maintain the pressure no more than -0.05MPa; (3) Turn on the current. After the arc is successfully struck, adjust the height of the arc gun electrode from the metal to 9-10 mm. First, melt the titanium block, then melt the metal raw materials placed in the crucible until they are completely melted. After the alloy ingot cools down, turn the newly melted ingot over and continue melting. Repeat this process several times until the structure is uniform. (4) Wait for the alloy ingot to cool to room temperature, open the air valve to let in air, then open the furnace door and take out the formed high-entropy alloy ingot.
[0008] Preferably, the atomic percentage of the high entropy alloy in step (1) is: Al 20%~26%, Cr 30%~34%, Co 30%~34%, Ni 16%~22%, and the formulation system is within the inflection curve of the free energy-composition curve.
[0009] More preferably, the purity of the pure metal raw materials of Al, Cr, Co and Ni in step (1) is above 99.9 wt.%.
[0010] Preferably, the vacuuming and filling with argon in step (2) are repeated 2 to 3 times.
[0011] Preferably, in step (3), the current for melting the titanium block is 200-300 A, and the current for melting the high entropy alloy ingot is 200-380 A.
[0012] More preferably, the time for melting the titanium block in step (3) is 1 to 2 min, and the time for melting the high entropy alloy ingot each time is 1 to 3 min.
[0013] More preferably, the number of times of turning and re-melting in step (3) is 3 to 5 times.
[0014] Preferably, the high entropy alloy prepared in step (4) is a single BCC phase without a second phase formed by element precipitation or heterogeneous nucleation.
[0015] Most preferably, in step (3) and step (4), the high entropy alloy can spontaneously produce uphill diffusion and nucleusless transformation during the melting-cooling process, and finally form a spinodal decomposition structure of Ni-rich, Al and Ni-poor, Al with large dispersion, uniform distribution and periodic variation.
[0016] 2. Microstructure Characterization of High Entropy Alloys Figure 1 The Al prepared in Examples 1 to 3 is given. 22 Cr 30 Co 30 Ni 18 、Al 24 Cr 30 Co 30 Ni 16 and Al 22 Cr31 Co 31 Ni 16 The XRD patterns of the three high entropy alloys show that they are all composed of a single BCC phase, without any diffraction peaks of any other phases. This indicates that the formulation system and preparation method of the present invention are used to prepare a new type of high entropy alloy whose crystal structure is completely different from the disclosed materials such as CN115505811B, and no impurities caused by element precipitation or heterogeneous nucleation are generated, which is conducive to maintaining a homogeneous structure, thereby producing consistent deformation or resistance to deformation under cavitation load impact.
[0017] Figure 2 The Al prepared in Example 1 is given. 22 Cr 30 Co 30 Ni 18 The dark field TEM image of the high entropy alloy represented by and the corresponding element surface distribution map. It can be clearly observed from the figure that at the nanoscale, the high entropy alloy grains are dispersed with periodically changing spinodal decomposition organizations, wherein the darker areas have higher Ni and Al content, while the brighter areas have lower Ni and Al content. This shows that since the four elements Al, Cr, Co and Ni used in the present invention have solubility intervals and the optimized ratio is just within the inflection curve of the free energy-composition curve, the uphill diffusion and non-nuclear transformation of Ni and Al elements are spontaneously generated during the melting-cooling process, and finally a typical spinodal decomposition organization is formed. This organizational structure is significantly different from the disclosed materials such as CN115505811B, which once again proves that the present invention obtains a completely new type of high entropy alloy by optimizing the element ratio.
[0018] Introducing spinodal decomposition structure into metal alloys can effectively inhibit dislocation movement, and is therefore considered an advanced technical approach to further improve material strength and hardness. However, this special organizational structure was previously believed to require a special heat treatment process to obtain (Materials Chemistry and Physics, 2020, 244, 122700), while the high-entropy alloy of the present invention does not require any subsequent heat treatment process. After simple melting and casting, a spinodal decomposition structure with large dispersion and uniform distribution can be obtained, proving that the element types and ratios optimized and selected by the present invention are very scientific and reasonable.
[0019] 3. Mechanical properties characterization of high entropy alloys A series of tests were conducted on the mechanical properties of the high entropy alloy of the present invention using a universal testing machine, a nanoindenter and a microhardness tester. Figure 3 The room temperature compressive stress-strain curve of the material is given. Figure 4 Their nanoindentation loading-unloading curves are given. Figure 5Their microhardness is given. It can be seen that the ultimate compressive strength of the high entropy alloy of the present invention is as high as 1.8~2.2 GPa, the nanohardness is as high as 7.9~8.7 GPa, and the microhardness is also in the range of 638~677 HV 0.1 These data are not only significantly higher than those of the Al2O3 prepared in Comparative Examples 1 and 2, which is mainly composed of FCC phase. 10 Cr 28 Co 28 Ni 34 High entropy alloys and FCC+BCC dual-phase Al 14 Cr 28 Co 28 Ni 30 High entropy alloys are also significantly higher than traditional BCC phase high entropy alloys (Materials Science and Engineering: A, 2016, 674, 203-211). 10 Cr 28 Co 28 Ni 34 The yield strength, nanohardness and microhardness of the high entropy alloy are only 337.3 MPa, 4.1 GPa and 274.1 HV respectively. 0.1 , while FCC+BCC dual phase Al 14 Cr 28 Co 28 Ni 30 The yield strength, nanohardness and microhardness of the high entropy alloy are only 499.2 MPa, 4.7 GPa and 321.4 HV respectively. 0.1 , respectively, about 2 to 6 times lower than the high entropy alloy of the present invention.
[0020] The above mechanical properties test results show that the high entropy alloy of the present invention can effectively resist dislocation movement due to its special spinodal decomposition structure, and exhibits extremely high strength and hardness.
[0021] 4. Cavitation and Cavitation-Corrosion Properties of High Entropy Alloys Referring to GB / T 6383-2009 standard, the cavitation and cavitation-corrosion performances of the high entropy alloy of the present invention, the high entropy alloy prepared in Comparative Examples 1 and 2, and ZG230-450H cast steel (a common metal material for flow-through parts) were tested using an ultrasonic vibration cavitation tester. The results are as follows: Figure 6As shown. The cumulative mass losses of the high entropy alloys prepared in Examples 1 to 3 after accelerated cavitation in deionized water for 40 h were only 0.1 mg, 0.2 mg and 0.2 mg, respectively, showing a nearly "zero damage" characteristic, indicating that because the high entropy alloys of the present invention have extremely high strength and hardness, they can completely withstand the impact of cavitation loads, that is, the impact force generated by the collapse of cavitation bubbles in the liquid can hardly cause any damage to the high entropy alloys of the present invention, showing unparalleled long-term anti-cavitation performance. Their cumulative mass losses after accelerated cavitation in artificial seawater for 40 h were only 0.6 mg, 0.5 mg and 0.6 mg, respectively, indicating that although seawater corrosion will accelerate material damage to a certain extent, the degree is not large, and its cavitation-corrosion resistance is still significantly superior to other materials.
[0022] The cumulative mass losses of comparative examples 1~2 and ZG230-450H cast steel after accelerated cavitation for only 10 h in deionized water were as high as 1.4 mg, 2.1 mg and 59.8 mg, respectively, while the cumulative mass losses after accelerated cavitation for the same time in artificial seawater were even higher, namely 2.2 mg, 2.9 mg and 62.3 mg, respectively.
[0023] It is not difficult to find that the high entropy alloy of the present invention has an ability to resist cavitation that is unmatched by existing metal alloy materials, whether in deionized water or artificial seawater.
[0024] In summary, the present invention has the following advantages compared with the prior art: The present invention scientifically utilizes the solubility intervals between the four metal elements of Al, Co, Cr, and Ni, and optimizes their respective ratios so that the alloy components are located within the inflection curve of the free energy-composition curve, so that the alloy system can spontaneously produce uphill diffusion and nucleusless transformation during vacuum arc melting, thereby forming a single BCC phase high entropy alloy with large dispersion and uniform distribution of spinodal decomposition structure. This is different from most metal alloys with spinodal decomposition structures that require special heat treatment processes, and is even more different from the single-phase FCC and dual-phase FCC+BCC crystal structures of existing Al-Cr-Co-Ni high entropy alloys. More importantly, the high entropy alloy of the present invention does not require any subsequent heat treatment and deformation strengthening treatment. It only relies on the spinodal decomposition structure in the BCC phase, and the ingot exhibits an ultimate compressive strength of 1.8~2.2GPa, a nanohardness of 7.9~8.7GPa, and a hardness of 638~677 HV 0.1 It has a microhardness of 1.18mm and exhibits long-term anti-cavitation and anti-cavitation-corrosion properties of "near zero damage" and "extremely slight damage" in deionized water and artificial seawater. Therefore, it is suitable for being directly made into various special-shaped flow-through components such as impellers, thrust bearings, and brackets for commercial application, and is expected to greatly improve the service life and operating stability of related components and equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the XRD spectrum of the high-strength, high-hardness and high-entropy alloy of the present invention.
[0026] Figure 2 It is a dark field TEM image of the high-strength, high-hardness and high-entropy alloy of the present invention and the corresponding element surface distribution map.
[0027] Figure 3 The room temperature compressive stress-strain curves of the high-strength, high-hardness, high-entropy alloy of the present invention and the comparative example.
[0028] Figure 4 Nanoindentation loading-unloading curves of the high-strength, high-hardness, high-entropy alloy of the present invention and the comparative example.
[0029] Figure 5 The microhardness of the high-strength, high-hardness and high-entropy alloy of the present invention and the comparative example.
[0030] Figure 6 The cavitation cumulative loss curves of the high-strength, high-hardness, high-entropy alloy of the present invention and the comparative example in deionized water and artificial seawater respectively. DETAILED DESCRIPTION
[0031] The present invention is further explained below with reference to specific embodiments.
[0032] Example 1 (1) Select Al, Cr, Co, and Ni metal raw materials with a purity of 99.99%, and mix them according to the atomic percentage: Al 22%; Cr 30%; Co 30%; Ni 18%. Before mixing, the oxide film and impurities on the surface of the raw materials are cleaned. When mixing, the atomic ratio is converted into the percentage of the mass of each element in the total mass for weighing; the Al, Cr, Co, and Ni metal raw materials are piled in a copper crucible of a vacuum arc melting furnace, and a titanium block is placed in another copper crucible to absorb oxygen, and the chamber door is closed.
[0033] (2) The smelting equipment is vacuumed to 5×10 -3 Pa, and then filled with argon to -0.05 MPa; this process was repeated 3 times.
[0034] (3) Turn on the current. After the arc is successfully struck, adjust the height of the arc gun electrode from the metal to 9-10 mm. First, melt the pure titanium block, keep the current at 220 A, and melt for 1 min; then move the arc gun to the position of the Al, Cr, Co, and Ni metal raw materials, and melt them until they are all melted. The melting time is 1-2 min, and the current is 290-330 A. After the alloy ingot cools down, turn the newly melted ingot over by rotating the mechanical arm. For each alloy ingot, turn it over 4 times, that is, melt it 5 times.
[0035] (4) In Al 22 Cr 30 Co 30 Ni 18 After the high entropy alloy is smelted, wait for the copper crucible to cool down, open the air valve to let in air, then open the chamber door to take out the formed high entropy alloy ingot.
[0036] (5) Al 22 Cr 30 Co 30 Ni 18 Structural properties of high entropy alloy ingots: The crystal structure is a single BCC phase, and has a dispersed and uniform amplitude modulation decomposition structure; the room temperature ultimate compressive strength is 2.2 GPa, the nanohardness is 8.7 GPa, and the microhardness is 677HV 0.1 , showing outstanding characteristics of high strength and hardness; the cumulative mass losses after cavitation in deionized water and artificial seawater for 40 h were 0.1 mg and 0.6 mg, respectively, showing extremely excellent long-term anti-cavitation and anti-cavitation-corrosion properties.
[0037] Example 2 (1) Select Al, Cr, Co, and Ni metal raw materials with a purity of 99.99%, and mix them according to the atomic percentage: Al 24%; Cr 30%; Co 30%; Ni 16%. Before mixing, the oxide film and impurities on the surface of the raw materials are cleaned. When mixing, the atomic ratio is converted into the percentage of the mass of each element in the total mass for weighing; the Al, Cr, Co, and Ni metal raw materials are piled in a copper crucible of a vacuum arc melting furnace, and a titanium block is placed in another copper crucible to absorb oxygen, and the chamber door is closed.
[0038] (2) The smelting equipment is vacuumed to 7×10 -3 Pa, and then filled with argon to -0.05 MPa; this process was repeated 3 times.
[0039] (3) Turn on the current. After the arc is successfully struck, adjust the height of the arc gun electrode from the metal to 9-10 mm. First, melt the pure titanium block, keep the current at 220 A, and melt for 1 min; then move the arc gun to the position of the Al, Cr, Co, and Ni metal raw materials, and melt them until they are completely melted. The melting time is 1-2 min, and the current is 280-340 A. After the alloy ingot cools down, turn the newly melted ingot over by rotating the mechanical arm. For each alloy ingot, turn it over 4 times, that is, melt it 5 times.
[0040] (4) In Al 24 Cr 30 Co 30 Ni 16After the high entropy alloy is smelted, wait for the copper crucible to cool down, open the air valve to let in air, then open the chamber door to take out the formed high entropy alloy ingot.
[0041] (5) Al 24 Cr 30 Co 30 Ni 16 Structural properties of high entropy alloy ingots: The crystal structure is a single BCC phase, and has a dispersed and uniform amplitude modulation decomposition structure; the room temperature ultimate compressive strength is 1.8 GPa, the nanohardness is 8.3 GPa, and the microhardness is 638HV 0.1 , showing outstanding characteristics of high strength and hardness; the cumulative mass losses after cavitation in deionized water and artificial seawater for 40 h were 0.2 mg and 0.5 mg, respectively, showing extremely excellent long-term anti-cavitation and anti-cavitation-corrosion properties.
[0042] Example 3 (1) Select Al, Cr, Co, and Ni metal raw materials with a purity of 99.99%, and mix them according to the atomic percentage: Al 22%; Cr 31%; Co 31%; Ni 16%. Before mixing, the oxide film and impurities on the surface of the raw materials are cleaned. When mixing, the atomic ratio is converted into the percentage of the mass of each element in the total mass for weighing; the Al, Cr, Co, and Ni metal raw materials are piled in a copper crucible of a vacuum arc melting furnace, and a titanium block is placed in another copper crucible to absorb oxygen, and the chamber door is closed.
[0043] (2) The smelting equipment is vacuumed to 4×10 -3 Pa, and then filled with argon to -0.05 MPa; this process was repeated 3 times.
[0044] (3) Turn on the current. After the arc is successfully struck, adjust the height of the arc gun electrode from the metal to 9-10 mm. First, melt the pure titanium block, keep the current at 220 A, and melt for 1 min; then move the arc gun to the position of the Al, Cr, Co, and Ni metal raw materials, and melt them until they are all melted. The melting time is 1-2 min, and the current is 270-320 A. After the alloy ingot cools down, turn the newly melted ingot over by rotating the mechanical arm. For each alloy ingot, turn it over 4 times, that is, melt it 5 times.
[0045] (4) In Al 22 Cr 31 Co 31 Ni 16 After the high entropy alloy is smelted, wait for the copper crucible to cool down, open the air valve to let in air, then open the chamber door to take out the formed high entropy alloy ingot.
[0046] (5) Al 22 Cr31 Co 31 Ni 16 Structural properties of high entropy alloy ingots: The crystal structure is a single BCC phase, and has a dispersed and uniform amplitude modulation decomposition structure; the room temperature ultimate compressive strength is 2.0 GPa, the nanohardness is 7.9 GPa, and the microhardness is 661HV 0.1 , showing outstanding characteristics of high strength and hardness; the cumulative mass losses after cavitation in deionized water and artificial seawater for 40 h were 0.2 mg and 0.6 mg, respectively, showing extremely excellent long-term anti-cavitation and anti-cavitation-corrosion properties.
[0047] Comparative Example 1 (1) Select Al, Cr, Co, and Ni metal raw materials with a purity of 99.99%, and mix them according to the atomic percentage: Al 10%; Cr 28%; Co 28%; Ni 34%. Before mixing, the oxide film and impurities on the surface of the raw materials are cleaned. When mixing, the atomic ratio is converted into the percentage of the mass of each element in the total mass for weighing; the Al, Cr, Co, and Ni metal raw materials are piled in a copper crucible of a vacuum arc melting furnace, and a titanium block is placed in another copper crucible to absorb oxygen, and the chamber door is closed.
[0048] (2) The smelting equipment is vacuumed to 5×10 -3 Pa, and then filled with argon to -0.05 MPa; this process was repeated 3 times.
[0049] (3) Turn on the current. After the arc is successfully struck, adjust the height of the arc gun electrode from the metal to 9-10 mm. First, melt the pure titanium block, keep the current at 220 A, and melt for 1 min; then move the arc gun to the position of the Al, Cr, Co, and Ni metal raw materials, and melt them until they are all melted. The melting time is 1-2 min, and the current is 290-330 A. After the alloy ingot cools down, turn the newly melted ingot over by rotating the mechanical arm. For each alloy ingot, turn it over 4 times, that is, melt it 5 times.
[0050] (4) In Al 10 Cr 28 Co 28 Ni 34 After the high entropy alloy is smelted, wait for the copper crucible to cool down, open the air valve to let in air, then open the chamber door to take out the formed high entropy alloy ingot.
[0051] (5) Al 10 Cr 28 Co 28 Ni 34Structural properties of high entropy alloy ingots: The crystal structure is mainly FCC phase, without uniform amplitude modulation decomposition structure; the room temperature yield strength is 337.3 MPa, the nanohardness is 4.1 GPa, and the microhardness is 274.1HV 0.1 , the hardness and strength are significantly lower than those of the high entropy alloy of the present invention; the cumulative mass loss after cavitation in deionized water and artificial seawater for 10 h is 1.4 mg and 2.2 mg respectively, which is significantly higher than that of the high entropy alloy of the present invention. This shows that even if the types of elements are the same, if the atomic percentage of each component in the high entropy alloy is not within the range specified in the present invention, a single BCC structure with spinodal decomposition organization cannot be prepared, the high entropy alloy will not have the characteristics of high strength and hardness, and the cavitation resistance and cavitation-corrosion resistance will be significantly deteriorated.
[0052] Comparative Example 2 (1) Select Al, Cr, Co, and Ni metal raw materials with a purity of 99.99%, and mix them according to the atomic percentage: Al 14%; Cr 28%; Co 28%; Ni 30%. Before mixing, the oxide film and impurities on the surface of the raw materials are cleaned. When mixing, the atomic ratio is converted into the percentage of the mass of each element in the total mass for weighing; the Al, Cr, Co, and Ni metal raw materials are piled in a copper crucible of a vacuum arc melting furnace, and a titanium block is placed in another copper crucible to absorb oxygen, and the chamber door is closed.
[0053] (2) The smelting equipment is vacuumed to 5×10 -3 Pa, and then filled with argon to -0.05 MPa; this process was repeated 3 times.
[0054] (3) Turn on the current. After the arc is successfully struck, adjust the height of the arc gun electrode from the metal to 9-10 mm. First, melt the pure titanium block, keep the current at 220 A, and melt for 1 min; then move the arc gun to the position of the Al, Cr, Co, and Ni metal raw materials, and melt them until they are all melted. The melting time is 1-2 min, and the current is 290-330 A. After the alloy ingot cools down, turn the newly melted ingot over by rotating the mechanical arm. For each alloy ingot, turn it over 4 times, that is, melt it 5 times.
[0055] (4) In Al 14 Cr 28 Co 28 Ni 30 After the high entropy alloy is smelted, wait for the copper crucible to cool down, open the air valve to let in air, then open the chamber door to take out the formed high entropy alloy ingot.
[0056] (5) In Al 14 Cr 28 Co 28 Ni 30Structural properties of high entropy alloy ingots: The crystal structure is FCC+BCC dual phase, without uniform amplitude modulation decomposition structure; the room temperature yield strength is 499.2 MPa, the nanohardness is 4.7 GPa, and the microhardness is 321.4HV 0.1 , hardness and strength are significantly lower than the high entropy alloy of the present invention; its cumulative mass loss after cavitation in deionized water and artificial seawater for 10 h is 2.1 mg and 2.9 mg respectively, which is significantly higher than the high entropy alloy of the present invention. This shows that even if the elements are the same, if the atomic percentage of each component in the high entropy alloy is not within the range specified in the present invention, a single BCC structure with spinodal decomposition organization cannot be prepared, and even a multi-phase structure will appear. The high entropy alloy does not have the characteristics of high strength and hardness. Under the action of cavitation load, each phase will have the disadvantage of mismatched plastic deformation, and the cavitation resistance and cavitation-corrosion resistance will be significantly deteriorated.
[0057] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A high-strength, high-hardness, high-entropy alloy with spinodal decomposition structure, characterized in that: The high entropy alloy is a single BCC phase Al-Cr-Co-Ni quaternary high entropy alloy, and the contents of each element are as follows, calculated by atomic percentage: Al 20%~26%, Cr 30%~34%, Co 30%~34%, and Ni 16%~22%.
2. A high-strength, high-hardness, high-entropy alloy with spinodal decomposition structure as claimed in claim 1, characterized in that: The room temperature ultimate compressive strength of the high entropy alloy is 1.8-2.2 GPa, the nanohardness is 7.9-8.7 GPa, and the microhardness is 638-677 HV 0.1 .
3. A high-strength, high-hardness, high-entropy alloy with spinodal decomposition structure as claimed in claim 1, characterized in that: The cavitation weight loss of the high entropy alloy is no more than 0.2 mg / 40 h, and the cavitation-corrosion weight loss is no more than 0.6 mg / 40 h.
4. A method for preparing a high-strength, high-hardness, high-entropy alloy having a spinodal decomposition structure as claimed in claim 1, characterized in that: Including but not limited to vacuum arc melting process. Taking vacuum arc melting process as an example, the main preparation process is as follows: (1) Prepare pure metal raw materials containing Al, Cr, Co and Ni according to the mass percentage converted from the atomic percentage of the high entropy alloy, clean the crucible at the same time, then put the prepared raw materials into the crucible of a vacuum arc melting furnace, and place a titanium block in another crucible for absorbing oxygen; (2) Close the furnace door and evacuate the equipment to a vacuum degree of <1×10 -2 Pa, then fill with argon to maintain the pressure no more than -0.05MPa; (3) Turn on the current. After the arc is successfully struck, adjust the height of the arc gun electrode from the metal to 9-10 mm. First, melt the titanium block, then melt the metal raw materials placed in the crucible until they are completely melted. After the alloy ingot cools down, turn the newly melted ingot over and continue melting. Repeat this process several times until the structure is uniform. (4) Wait for the alloy ingot to cool to room temperature, open the air valve to let in air, then open the furnace door and take out the formed high-entropy alloy ingot.
5. The method for preparing a high-strength, high-hardness, high-entropy alloy having a spinodal decomposition structure according to claim 4, characterized in that: The purity of the pure metal raw materials of Al, Cr, Co and Ni in step (1) is above 99.9wt.%.
6. The method for preparing a high-strength, high-hardness, high-entropy alloy having a spinodal decomposition structure according to claim 4, characterized in that: In step (3), the current for melting the titanium block is 200-300A, and the current for melting the high entropy alloy ingot is 200-380A.
7. The method for preparing a high-strength, high-hardness, high-entropy alloy having a spinodal decomposition structure according to claim 4, characterized in that: In step (3), the melting is repeated 3 to 5 times.
Citation Information
Patent Citations
A high-entropy alloy based on Al-Cr-Co-Ni, its preparation method and application
CN115505811B